Investigation on the Influence of Moisture Content and Wood Section on the Frictional Properties of Beech Wood Surface. Issue 5 (3rd September 2021) - Fu, Weilian; Guan, Huiyuan; Chen, Bingrui
Abstract: To closely examine the mechanical properties of mortise and tenon woodworking joinery in outdoor environments, it is essential to obtain fundamental data regarding the influence of moisture content and wood section on the frictional properties of wood surfaces. In this study, the static and dynamic friction coefficients under varying moisture contents (5, 8.50, 11.25, 20, 30, 40, 50, and 60%) and wood sections (tangential, diagonal, and radial) were measured. Moreover, the equation for the relationship between moisture content and friction coefficient was obtained and variations in friction coefficients caused by the effects of moisture content and wood section on roughness and hardness were analyzed. The results showed that moisture content and wood section had significant effects on the friction coefficient of beech wood. With increasing moisture content, the static and dynamic friction coefficients both increased, and the tangential section exhibited a higher friction coefficient than the diagonal and radial sections. Furthermore, with increasing moisture content, the ratio of the dynamic friction coefficient to the static friction coefficient showed an initial increasing trend and then gradually flattened due to the stick–slip effect, and the friction coefficient showed a segmented and positive growth trend in the moisture content range of 5–60%. Ultimately, it was found that higher moisture contents had a negative effect on frictional properties, leading to rougher wood surfaces and lower hardness, and roughness was linearly correlated with the friction coefficient. These findings can assist in making accurate calculations and optimizing the structural design of wood products.